Experimental antiviral therapy against different rabies virus lineages using transfection with anti-rabies antibodies (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The aim of this study was to develop a new mechanism for antiviral therapy against rabies based on the introduction by transfection with a cationic reagent (lipofectamine 2000) of antibodies into neuronal cells infected with the rabies virus. N2A cells were infected using 96-well plates and different viral concentrations (0.1, 1.0, 10 and 100 TCID50) of three lineages of rabies virus circulating in Brazil (dog, Desmodus rotundus and Eptesicus furinalis). After incubation for 24 h, the cells were transfected with antirabies- virus polyclonal antibodies and lipofectamine 2000. These cells made up the treatment group (TG). The cells in the negative control group (CG) were treated with only Minimum Essential Medium. After 11 hours, the plates were fixed with 80% acetone and analyzed by direct immunofluorescence using a fluorescein isothiocyanateconjugated antinucleocapsid rabies antibody. The effectiveness of the transfection and subsequent neutralization of the virus was determined by calculating the percentage inhibition of fluorescent foci. This was done by measuring the difference in the number of fluorescent foci in the two groups (CG and TG). The results show that for lower viral concentrations (0.1 and 1.0 TCID50), viral inhibition was 100% for all the lineages tested. When higher virus concentrations were used (10 and 100 TCID50), inhibition varied according to the viral load and lineage of rabies virus used. With an infectious dose of TCID50, inhibition varied from 82.7% to 100% for the lineages tested. With a 100 TCID50 dose, inhibition was 90.7% for the D. rotundus lineage, 90.3% for the dog lineage and 67.0% for the E. furinalis lineage. It can be concluded from these results that, irrespective of the viral load the patient is exposed to, transfection with antibodies is an efficient mechanism for use in antiviral therapy against rabies in cases where the transmitter is the hematophagous bat D. rotundus or the dog as inhibition only varied from 89.2% to 100% when these lineages were used. However, if the patient has been exposed to the lineage associated with the insectivorous bat E. furinalis, inhibition varies with viral load. These findings show that transfection with antibodies is a promising mechanism that could be used to develop an antiviral therapy against rabies. Further studies are required to assess the efficiency of transfection with antibodies in vivo.